A protocol for selection of Trichoderma spp. to protect grapevine pruning wounds against Lasiodiplodia theobromae - Marraschi, Renata; Ferreira, Ana Beatriz Monteiro; da Silva Bueno, Roselaine Nunes; Leite, Juliana A. B. P.; Lucon, Cleusa Maria Mantovanello; Harakava, Ricardo; Leite, Luís Garrigós; Padovani, Carlos Roberto [UNESP]; Bueno, César Júnior (Springer Nature, 2019)
There is no standardized protocol to select Trichoderma against trunk disease pathogens in grapevine. This study describes a protocol to select Trichoderma isolates for protecting the pruning wounds of grapevine against Lasiodiplodia theobromae. Thus, four assays were performed: (1) in vitro antagonism of Trichoderma isolates, molecularly identified, to control L. theobromae; (2) in vitro effect of grapevine fungicides on the conidia of the antagonists; (3) capability of Trichoderma to survive and endophytically penetrate in grapevine canes; and (4) efficiency of Trichoderma and fungicides to protect the pruning wounds of grapevine shoots against L. theobromae. T. asperelloides (02/03), T. koningiopsis (09/02), and T. asperellum (01/13) were the best antagonists for L. theobromae. The conidia of the three isolates were affected only by tebuconazole, with the first two fungi being the most tolerant to the fungicides. The Trichoderma isolates survived on the cane tip for 15 days, but only T. asperelloides (02/03) penetrated endophytically 4 cm in the cane and showed preventive and curative capability to control L. theobromae, with similar efficiency as that of the fungicides in both the periods tested post inoculation. These four assays are suggested to select Trichoderma against L. theobromae or other trunk disease pathogens.
Keywords: Biocontrol; Decline; Fungicides; Niagara Rosada